Prevalence of depression and its association with suicidal ideation among older people - Syed Elias, Sharifah Munirah; Ahmad Tarmidi, Nor Hazwani; Makhtar, Aniawanis (2019)
Objective: Suicidal ideation is common in older people worldwide. However, there is a lack of data about suicidal ideation and its risk factor among Malaysian population. Aims: To determine the prevalence of suicidal ideation and depressive symptoms, and risk factors contributing to suicidal ideation among older people.Methods: A cross sectional study was conducted on 200 older people aged 60 years and older who attended Medical Outpatient Department (MOPD) Hospital Tengku Ampuan Afzan, Kuantan. A questionnaire consisted of three parts; (1) Socio demographic background, (2) Depressive symptoms (Geriatric Depression Scale (GDS-15) and (3) Suicide Behaviors Questionnaire Revised (SBQ-R). The data were analyzed by Statistical Package Social Sciences (SPSS) version 20.Results: The prevalence rate of older people who experienced suicidal ideation was 3% and 29.5 % older people reported depression. It was found that there was an association between ethnicity (p < 0.00), marital status (p= 0.008), depressive symptoms (p < 0.00) and suicidal ideation. Conclusion: Ethnicity, marital status and depressive symptoms are associated with suicidal ideation among older people in Malaysia. Future interventions should focus on these factors while planning for the intervention specific for this group of older people.